2006
DOI: 10.1111/j.1365-263x.2006.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment of children referred to general anaesthesia – association with country of origin and medical status

Abstract: Age at treatment, waiting times in the system, and dental treatment received under general anaesthesia vary according to medical status and country of origin of the patients in Denmark. These findings should be considered in the organization and the funding of this type of service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
9
17
2
Order By: Relevance
“…Vitamin D deficiency was observed to a much higher extent among immigrants, especially girls, compared to ethnic Danes [10,11]. Oral health was also poorer with higher percentage of caries in immigrant and descendant children compared with ethnic Danes [12,13].…”
Section: Childrenmentioning
confidence: 86%
“…Vitamin D deficiency was observed to a much higher extent among immigrants, especially girls, compared to ethnic Danes [10,11]. Oral health was also poorer with higher percentage of caries in immigrant and descendant children compared with ethnic Danes [12,13].…”
Section: Childrenmentioning
confidence: 86%
“…This finding agrees with a report in which patients with special needs were older when treated than non-special needs patients. 22 This could be explained due that most patients come from low-income families that lived in small communities in several states of the central area of Mexico with difficulties for transportation to DGA setting; this situation produce a delay of information, waiting time and economical difficulties to deliver DGA procedures. Besides, most MCDD children have complicated health needs with high priority for the family as a result produces a later referral for dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] There is not a clear explanation for this difference in gender distribution, but it has been suggested that a higher prevalence of neuropsychiatric disorders among boys could explain the predominance of males. 22 It has been reported that in hospital settings, the frequency of DGA is concentrated in patients affected with cardiac problems, asthma, physical and emotional disabilities. 28 However, in a study carried out in Spain it was reported that the main frequency of oral rehabilitations under DGA were in intellectual disability, cerebral palsy, epilepsy, and Down syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However disabled patients' pattern of age, treatment need and caries experience is not proportional, as one can imagine, to the severity of the impairing condition. Haubek et al (18) report that, in a group of patients who underwent to general anesthesia for dental treatment, special needs children "were older at referral and had a less comprehensive total treatment need than non-special needs patients", supporting as a possible explanation that attention to preventive oral health attitude is often paid by caregivers and specialized personnel, so that these children develop a treatment need only at higher ages. Similarly, Camilleri et al (19), compared the level of dental disease and the pattern of dental treatment under general anesthesia for children with different ASA Physical Status Classification System level.…”
Section: Oral Health Prevention and Treatment Issuesmentioning
confidence: 99%